Exudates from Miscanthus x giganteus change the response of a root-associated Pseudomonas putida strain towards heavy metals. (15th November 2022) - Zadel, Urška; Cruzeiro, Catarina; Raj Durai, Abilash Chakravarthy; Nesme, Joseph; May, Robert; Balázs, Helga; Michalke, Bernhard; Płaza, Grażyna; Schröder, Peter; Schloter, Michael; Radl, Viviane
Abstract: The composition of root exudates is modulated by several environmental factors, and it remains unclear how that affects beneficial rhizosphere or inoculated microorganisms under heavy metal (HM) contamination. Therefore, we evaluated the transcriptional response of Pseudomonas putida E36 (a Miscanthus x giganteus isolate with plant growth promotion-related properties) to Cd, Pb and Zn in an in vitro study implementing root exudates from M. x giganteus . To collect root exudates and analyse their composition plants were grown in a pot experiment under HM and control conditions. Our results indicated higher exudation rate for plants challenged with HM. Further, out of 29 organic acids identified and quantified in the root exudates, 8 of them were significantly influenced by HM (e.g., salicylic and terephthalic acid). The transcriptional response of P. putida E36 was significantly affected by the HM addition to the growth medium, increasing the expression of several efflux pumps and stress response-related functional units. The additional supplementation of the growth medium with root exudates from HM-challenged plants resulted in a downregulation of 29% of the functional units upregulated in P. putida E36 as a result of HM addition to the growth medium. Surprisingly, root exudates + HM downregulated the expression of P. putida E36 functional units related to plant colonization (e.g., chemotaxis, motility, biofilm formation) but upregulated its antibiotic and biocide resistance compared to the control treatment without HM. Our findings suggest that HM-induced changes in root exudation pattern may attract beneficial bacteria that are in turn awarded with organic nutrients, helping them cope with HM stress. However, it might affect the ability of these bacteria to colonize plants growing in HM polluted areas. Those findings may offer an insight for future in vivo studies contributing to improvements in phytoremediation measures. Graphical abstract: Image 1 Highlights: Heavy metal (HM) treatment of Miscanthus x giganteus increased root exudation. Salicylic and terephthalic acid concentrations increased in metal-treated plants. putida E36 responded differently to HM stress in presence or absence of root exudates. Presence of heavy metals affected P. putida expression of plant colonization traits.